2017
DOI: 10.1111/ffe.12680
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction between corrosion and fatigue which determines the remaining life of bridges

Abstract: This paper studies the prior effect of corrosion on fatigue on the growth of cracks that arise from natural corrosion in steel bridges. It is shown that these 2 effects need to be simultaneously analysed. If not, then the resulting life is not conservative. This paper presents a simple methodology for performing this coupled analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Indeed, this finding is independently validated via the recent review of atomistic simulation of the growth of small cracks [52,53]. As explained in ASTM E647-13a [54] and [8,19,20,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]53], for crack growth from small naturally occurring discontinuities there is little R ratio dependence and the value of ∆Kthr is very small . Hence there is little, if any, crack closure associated with the growth of small naturally occurring cracks [8,19,53].…”
Section: Discussion Of Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Indeed, this finding is independently validated via the recent review of atomistic simulation of the growth of small cracks [52,53]. As explained in ASTM E647-13a [54] and [8,19,20,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]53], for crack growth from small naturally occurring discontinuities there is little R ratio dependence and the value of ∆Kthr is very small . Hence there is little, if any, crack closure associated with the growth of small naturally occurring cracks [8,19,53].…”
Section: Discussion Of Resultsmentioning
confidence: 71%
“…The values of ΔKthr used as well as the initiating discontinuity size are shown in Table 5. The results of this study when taken in conjunction with that in Section 2 and the studies presented in [6,8,19,20,26,4238,41,42] illustrate how the growth of cracks from environmental damage in aircraft structures can be reasonably accurately computed using the Hartman-Schijve crack growth equation and that allowing for experimental error the variability of the crack depth histories can be reasonably well accounted for by allowing for small changes in the value of the term Kthr. We also see that, as per the USAF approach to ris  k assessment [16] and the DST Group formulation [17,18] the growth of the lead cracks, i.e.…”
Section: Crack Growth At Fastener Holes Containing Intergranular Cracmentioning
confidence: 66%
See 1 more Smart Citation
“…Xu et al [20] also studied the fatigue behavior of corroded steel, which indicated that the fatigue life of corroded steel decreased rapidly due to the increasing rough surface. Peng et al [25,26] combined the uniform corrosion and NASGRO equation to determine the remaining life of structures, the result indicated that the C-F life of the structure was decreased with the assumed initial flaw size increasing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As far as metallic materials are concerned, many structural components experience multiaxial fatigue loading. This is the case, for instance, of metallic parts of bridges cyclically loaded by traveling motor vehicles …”
Section: Introductionmentioning
confidence: 99%